What have corporations got to do with it? A political economy approach to organizations and climate change - Annika Rieger (economic sociology. perspectives and conversations, 2024)
Ecological issues are often seen as only one of the many "problems" societies face today, even though they go deep and affect everything - from physical disruption and displacement to perhaps more subtle long-term changes in temperature, flora, and fauna that alter the face of the planet and the norms of everyday life. As a result of this view, the study of the environment has been siloed into the realm of "environmental sciences" with a few "environmental fill-in-the-social-science-blank" subfields scattered about. This is not to say that only "environmental" problems are important, but that across all disciplines and subfields, greater attention needs to be paid to these issues - especially to the ways in which environmental problems intersect with other social problems, including those of race, gender, and class.
Keywords: 300